Identifying the Dimensions of Love in Adolescence from the Perspective of Adolescents in Qazvin Province: A Study Based on Grounded Theory - Ghafoori, Arezu; Shariat Bagheri, Mohammad Mahdi; Salehi, Keyvan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and analyze the dimensions of adolescent love from the perspective of teenagers in Qazvin Province using grounded theory and Schatzman’s dimensional analysis. Methods and Materials: A qualitative research design based on grounded theory was employed to explore adolescents’ lived experiences of love. Thirty adolescents (aged 13–18) were selected through purposive sampling, and semi-structured interviews were conducted along with the collection of ten written letters. The interviews and texts were analyzed using Schatzman’s dimensional analysis, encompassing five key dimensions: perspective, context, conditions, process, and outcomes. Theoretical saturation guided the termination point of data collection. The core category that emerged—“navigating the season of adolescence”—served as the theoretical lens through which the other categories were integrated. Credibility was ensured through member checking, peer debriefing, and prolonged engagement with participants. Findings: The study identified 36 primary categories grouped under nine major subdimensions. Adolescents described their romantic experiences as beginning with attraction and emotional curiosity, progressing through stages of affection, connection, conflict, and either resolution or dissolution. The findings highlighted both positive outcomes—such as increased self-confidence, emotional growth, and improved social skills—and negative consequences including emotional instability, academic decline, and psychological distress following breakups. Trust and perceived similarity emerged as critical preconditions for forming and sustaining romantic connections. The family’s communication style and emotional support level played significant roles in shaping relational behavior and coping mechanisms. Conclusion: Adolescent love is a complex, multifaceted phenomenon influenced by emotional, social, and contextual variables. It serves as both a developmental challenge and a transformative opportunity. Understanding its structure and consequences can inform educational, psychological, and familial interventions aimed at promoting healthy relational development during adolescence.